The Provocative Roles of Platelets in Liver Disease and Cancer - Kanikarla Marie, Preeti; Fowlkes, Natalie W.; Afshar-Kharghan, Vahid; Martch, Stephanie L.; Sorokin, Alexey; Shen, John Paul; Morris, Van K.; Dasari, Arvind; You, Nancy; Sood, Anil K.; Overman, Michael J.; Kopetz, Scott; et al. (Frontiers in Oncology, 2021)
Both platelets and the liver play important roles in the processes of coagulation and innate immunity. Platelet responses at the site of an injury are rapid; their immediate activation and structural changes minimize the loss of blood. The majority of coagulation proteins are produced by the liver—a multifunctional organ that also plays a critical role in many processes: removal of toxins and metabolism of fats, proteins, carbohydrates, and drugs. Chronic inflammation, trauma, or other causes of irreversible damage to the liver can dysregulate these pathways leading to organ and systemic abnormalities. In some cases, platelet-to-lymphocyte ratios can also be a predictor of disease outcome. An example is cirrhosis, which increases the risk of bleeding and prothrombotic events followed by activation of platelets. Along with a triggered coagulation cascade, the platelets increase the risk of pro-thrombotic events and contribute to cancer progression and metastasis. This progression and the resulting tissue destruction is physiologically comparable to a persistent, chronic wound. Various cancers, including colorectal cancer, have been associated with increased thrombocytosis, platelet activation, platelet-storage granule release, and thrombosis; anti-platelet agents can reduce cancer risk and progression. However, in cancer patients with pre-existing liver disease who are undergoing chemotherapy, the risk of thrombotic events becomes challenging to manage due to their inherent risk for bleeding. Chemotherapy, also known to induce damage to the liver, further increases the frequency of thrombotic events. Depending on individual patient risks, these factors acting together can disrupt the fragile balance between pro- and anti-coagulant processes, heightening liver thrombogenesis, and possibly providing a niche for circulating tumor cells to adhere to—thus promoting both liver metastasis and cancer-cell survival following treatment (that is, with minimal residual disease in the liver).